Interpretation of Basic and Advanced Urodynamics - Firoozi, Farzeen (Springer International Publishing : Imprint: Springer, 2017)
This book provides a comprehensive, state-of-the-art review of this evaluation of voiding disorders and will serve as a valuable resource for clinicians and surgeons. The book reviews the basic indications for urodynamics as well as the interpretation of basic and advanced studies with the use of clinical vignettes. In addition to step-by-step description in text, the textbook provides illustrations/photographs and tracings of different urodynamics scenarios. This atlas of urodynamics will serve as an extremely useful resource for physicians dealing with and interested in the evaluation of pelvic floor disorders and voiding dysfunction. It will provide a concise and comprehensive review of all the different types of urodynamics scenarios, while instructing its readers on how to accurately and consistently interpret these studies. All chapters are written by experts in the fields of pelvic floor disorders and voiding dysfunction.
Keywords: Medicine.; Gynecology.; Urology.; elektronické knihy; electronic books